Characteristics of Body Composition Estimated by Air-Displacement Plethysmography in Chinese Preschool Children - Fangfang Chen; Jing Wang; Junting Liu; Guimin Huang; Dongqing Hou; Zijun Liao; Ting Zhang; Gongshu Liu; Xianghui Xie; Jun Tai (Frontiers in Public Health, 2022)
ObjectiveTo describe the characteristics of body composition by air-displacement plethysmography (ADP) among Chinese preschool children.MethodsPreschool children were recruited from three kindergartens. Adiposity indices were evaluated using the ADP method. BMI, fat mass index (FMI), fat-free mass index (FFMI) and waist-to-height ratio (WHtR) were calculated. Overweight and obesity were diagnosed using the WHO reference. Analyses were executed by SPSS and MedCalc software. Smoothed curves were constructed using the lambda-mu-sigma (LMS) method.ResultsThis study evaluated the growth trend for body composition of ADP-based body fat indices based on a relatively large sample of preschool children, the first ever reported in China. A total of 1,011 children aged 3–5 years comprised our study population. BMI and FFMI increased with age, but the slope (P = 0.710) and y intercept (P = 0.132) in the BMI trend analysis demonstrated no differences between boys and girls. For the FFMI trend lines, the slope was significantly higher for boys than for girls (P = 0.013). The percentage of fat mass (FM%), FMI, and WHtR were negatively correlated with age for both sexes, except for FMI in girls (P = 0.094). The 95% CI regression lines for FM% according to different weight statuses intersected.ConclusionsADP is applicable to estimating body composition among Chinese preschool children. Misclassifications might occur when overweight/obese status is defined based on surrogate indices.